2017
DOI: 10.1111/clr.13028
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of peri‐implantitis intrabony lesions by means of deproteinized bovine bone mineral with 10% collagen: 7‐year‐results

Abstract: Seven years after surgical treatment with DBBMC, patients, in an adequate SPT, maintained sufficient peri-implant conditions in many cases, particularly around SLA implants. Nevertheless, some patients required further treatment and some lost implants. The clinical decision on whether implants should be treated or removed should be based on several factors, including implant surface characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
152
5
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(177 citation statements)
references
References 24 publications
14
152
5
6
Order By: Relevance
“…This outcome was attained in this RCT in 66.7% of the implants in the test and in 23.1% of implants in the control group. Similar percentages have been reported in studies evaluating 5‐year evolution of surgical peri‐implantitis therapy (Heitz‐Mayfield et al., ; Leonhardt, Dahlen, & Renvert, ; Roos‐Jansaker, Persson, Lindahl, & Renvert, ; Serino, Turri, & Lang, ) and 7‐years evolution (Roccuzzo, Pittoni, Roccuzzo, Charrier, & Dalmasso, ; Schwarz et al., ). Although the results obtained in the test group (adjunctive use of the titanium brush) in this study can be comparable to the best outcomes of the previously cited reports, a longer follow‐up is needed to validate these outcomes, since regular supportive therapy and strict plaque control measures are needed to maintain the results long‐term (Isehed, Svenson, Lundberg, & Holmlund, ).…”
Section: Discussionsupporting
confidence: 81%
“…This outcome was attained in this RCT in 66.7% of the implants in the test and in 23.1% of implants in the control group. Similar percentages have been reported in studies evaluating 5‐year evolution of surgical peri‐implantitis therapy (Heitz‐Mayfield et al., ; Leonhardt, Dahlen, & Renvert, ; Roos‐Jansaker, Persson, Lindahl, & Renvert, ; Serino, Turri, & Lang, ) and 7‐years evolution (Roccuzzo, Pittoni, Roccuzzo, Charrier, & Dalmasso, ; Schwarz et al., ). Although the results obtained in the test group (adjunctive use of the titanium brush) in this study can be comparable to the best outcomes of the previously cited reports, a longer follow‐up is needed to validate these outcomes, since regular supportive therapy and strict plaque control measures are needed to maintain the results long‐term (Isehed, Svenson, Lundberg, & Holmlund, ).…”
Section: Discussionsupporting
confidence: 81%
“…The findings of the present study was particularly in line with a previous study reported by Renvert et al 45 that increased age could be as a negative contributory factor, when associated with history of periodontitis for the development of peri-implantitis. 5,8 Nonetheless, there has been no study to date which has been designed to assess the effect of implant surface characteristics. 46 The distribution of different implant systems and surface characteristics in the CGF and CM groups can be considered a limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recent systematic reviews of clinical trials have reported that regenerative surgical treatment (RST) of peri-implantitis has been shown to result in improvements in probing depth (PD) reduction, BOP and radiographic evidence of defect fill (DF). [3][4][5][6][7][8] Recent systematic reviews of clinical trials have reported that regenerative surgical treatment (RST) of peri-implantitis has been shown to result in improvements in probing depth (PD) reduction, BOP and radiographic evidence of defect fill (DF).…”
mentioning
confidence: 99%
“…Results from animal experiments have revealed that resolution of peri‐implantitis lesions using anti‐infective measures during surgical therapy is possible (Albouy, Abrahamsson, Persson, & Berglundh, ; Carcuac, Abrahamsson, Charalampakis, & Berglundh, ). In addition, data from clinical studies indicate that anti‐infective surgical treatment protocols also are effective in the long term (Berglundh, Wennström, & Lindhe, ; Carcuac et al, ; Heitz‐Mayfield et al, ; M. Roccuzzo, Pittoni, Roccuzzo, Charrier, & Dalmasso, ; Schwarz, John, Schmucker, Sahm, & Becker, ). Results from clinical and experimental studies also revealed that implant surface characteristics influenced outcomes of surgical treatment of peri‐implantitis (Albouy et al, ; Berglundh, Wennström, et al, ; Carcuac et al, ; Carcuac et al, ; Carcuac et al, ; M. Roccuzzo, Bonino, Bonino, & Dalmasso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the reconstructive procedures should result in bone fill of the osseous defect including re‐osseointegration and provide support to peri‐implant soft tissue and thereby improving esthetic outcomes. While bone substitute materials have been commonly used in reconstructive surgical therapy of peri‐implantitis (M. Roccuzzo et al, ; Roos‐Jansåker, Persson, Lindahl, & Renvert, ; Schwarz et al, ), controlled clinical studies investigating their potential benefit of enhancing results are few (Jepsen et al, ; Renvert, Roos‐Jansåker, & Persson, ; Wohlfahrt et al, ). In addition, experimental studies presenting data favoring the use of bone substitute materials to improve bone repair and/or re‐osseointegration appear to be lacking.…”
Section: Introductionmentioning
confidence: 99%